The Problems regarding the Provisional Release in Criminal Trial in Thailand: The Case Study of the Provisional Release without Bail - Kittiwattananon, Tutiyapong (Nitipat NIDA Law Journal, 2022)
Thailand is a member of the Universal Declaration of Human Rights (UDHR) and International Covenant on Civil and Political Rights (ICCPR), these two instruments have an important principle that were enacted, which is the presumption of innocence. As a result, Thailand has brought such principles into the domestic law such as the Constitution of the Kingdom of Thailand and criminal procedural law. However, in practice, especially in the matter of provisional release, although it has a satisfactory level of provisional release, but the statistics of provisional release without bail is very few. This article, therefore, aims to analyze the problems relating to provisional release in Thailand along with suggesting solutions by studying legal concepts and theories, including the provisional release system of the United States and United Kingdom (Scotland) to be applied to the law, including the provisional release system of Thailand to be more efficient and consistent with the presumption of innocence. The study found that the United States has a provisional release system using a risk assessment method and United Kingdom (Scotland) has a provisional release system using a supervised bail. The author, therefore, has the opinion that although Thailand has started to use the provisional release system by means of risk assessment but there are still some parts that can be modified to make it more effective, such as factors used in risk assessment. And if the supervised bail is adapted to the provisional release system that Thailand currently uses together with the amendment of the provisions of the law on the determination of bail to be in the same direction as the United States, which will result in the court unable to detain the accused or the defendant because there is no money or property to be placed according to the amount of bail. The author believes that it will make the law, including the provisional release system of Thailand, to be more efficient and consistent with the presumption of innocence doctrine.